2012
DOI: 10.1038/gene.2012.34
|View full text |Cite
|
Sign up to set email alerts
|

Decreased systemic IL-7 and soluble IL-7Rα in multiple sclerosis patients

Abstract: Polymorphisms (single-nucleotide polymorphism (SNP)) in the interleukin-7 receptor-a (IL-7Ra)/IL-7 pathway are associated with an increased risk to develop multiple sclerosis (MS). The rs6897932 SNP in the IL-7Ra leads to increased soluble IL-7Ra production. Given the functional interaction between sIL-7Ra, membrane-bound IL-7Ra and IL-7, we assessed IL-7, mIL-7Ra and sIL-7Ra levels in MS patients and healthy controls (HCs). One-hundred and twenty eight MS patients had significantly lower sIL-7Ra levels compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Fig. 1A), which is consistent with several previous findings (Kreft et al, 2012a; Kreft et al, 2012b). …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Fig. 1A), which is consistent with several previous findings (Kreft et al, 2012a; Kreft et al, 2012b). …”
Section: Resultssupporting
confidence: 93%
“…Our result is consistent with previous findings in which slightly but significantly decreased systemic IL-7 and a higher membrane to soluble IL-7Rα ratio on CD4 + and CD8 + cells were reported (Kreft et al, 2012a; Kreft et al, 2012b). However, these findings appear in contrast with the up-regulated IL-7 plasma levels observed by Hass et al (Haas et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, lower IL-7 serum levels were observed in active inflammatory bowel disease than in remission [27]. Also studies in patients with multiple sclerosis [28] and systemic scleroderma [29] have revealed lower serum levels of IL-7 than in controls. Our observations are consistent with those of previous study regarding expression of IL-7 in tears and orbital tissues of patients with Graves' ophthalmopathy (GO).…”
Section: Gd-total (N = 37) Gd-active (N = 15) Gd-inactive (N = 8) Gd-mentioning
confidence: 93%
“…The biological effects of IL-7 are mediated via the hematopoietic IL-7 receptor (IL-7R) complex, IL-7 receptor α chain, which binds IL-7 and thymic stromal lymphopoietin and the IL-2 receptor γ chain; it has been found to be a cofactor for V(D)J rearrangement of T-cell receptor beta during early T-cell development (Muegge et al, 1993). Recent studies have shown that polymorphisms at specific loci on the IL-7Rα were risk factors for a number of diseases, including multiple sclerosis, type 1 diabetes, rheumatoid arthritis, primary biliary cirrhosis, inflammatory bowel disease, atopic dermatitis, inhalation allergy, sarcoidosis, and graft-versus-host disease (Sombekke et al, 2011;Mazzucchelli et al, 2012;Kreft et al, 2012).…”
Section: Introductionmentioning
confidence: 99%